1995
DOI: 10.1139/f95-177
|View full text |Cite
|
Sign up to set email alerts
|

Size-related changes in diel distribution of young grayling (Thymallus thymallus)

Abstract: An approach based on direct observation from the riverbank allowed a precise description of the size-dependent distribution patterns of young grayling. The smallest larvae (15–20 mm) were mainly observed in the upper layers of the water column and very close to the riverbank. With increasing age and size (20–35 mm), old larvae and young parr began to hold positions closer to the bottom and to the edge of the main channel. From a size of 35–40 mm. an increasing number of juveniles were observed in the river cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 1 publication
7
39
1
Order By: Relevance
“…Grayling, however, were similarly affected by these factors only in winter. Larger grayling (>6 cm) are able to use much higher water velocities than their smaller conspecifics (Sempeski & Gaudin 1995, see also Valentin et al 1994; i.e. neither substrate complexity nor flow level induced downstream movement of grayling (mean length 7.6 cm) in our summer experiments.…”
Section: Microhabitat Selection By Trout and Grayling In Relation To supporting
confidence: 52%
See 1 more Smart Citation
“…Grayling, however, were similarly affected by these factors only in winter. Larger grayling (>6 cm) are able to use much higher water velocities than their smaller conspecifics (Sempeski & Gaudin 1995, see also Valentin et al 1994; i.e. neither substrate complexity nor flow level induced downstream movement of grayling (mean length 7.6 cm) in our summer experiments.…”
Section: Microhabitat Selection By Trout and Grayling In Relation To supporting
confidence: 52%
“…Juvenile brown trout mostly occupied positions with a snout water velocity less than 20 cm/s (as reviewed by Heggenes 1989). Such low velocities are also used by the smallest fry of grayling, but less frequently when their length exceeds 6 cm (Sempeski & Gaudin 1995). However, since both trout and grayling selected lower velocities in winter than in summer, the potential for interspecific competition may increase with decreasing water temperature.…”
Section: Microhabitat Selection By Trout and Grayling In Relation To mentioning
confidence: 99%
“…Some field and experimental studies have been concentrated on the potential overlap of diets and/or habitat requirements (MAITLAND, 1965;MANN and ORR, 1969;LIEN, 1981 ;NEVEU, 1981 ;BALTZ et al, 1982;WELTON et al, 1983;GLOVA, 1987;BROWN, 1991), but little is known about the temporal aspect of habitat use. On a seasonal scale, habitat shifts are closely related to the life history of species, like ontogenetic changes in habitat requirements (ELLIOTT, 1986 ;BAGLINIÈRE era/., 1989 ;BALTZ et al, 1991 ;SEMPESKI and GAUDIN, 1995 ;KOCIK and TAYLOR, 1996), spawning (BAGLINIÈRE era/., 1987 ;MEYERS et al, 1992) and overwintering migration (CUNJAK and POWER, 1986 ;SWALES ef a/., 1986 ;BROWN and MACKAY, 1995), whereas diel habitat shifts usually correspond to circadian rhythms of resting and feeding activities (CAMPBELL and NEUNER, 1985 ;KWAK et al, 1992 ;HEGGENES era/., 1993 ;ROUSSEL and BARDONNET, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…observed there. Rather, level-gentle banks may have a true functional role, possibly by providing shelter (Scott 1985) or by offering fry, a physical gradient along which to move from slow, shallow areas near shore at night to faster running, deeper areas close to the main channel by day (Sempeski & Gaudin 1995b). Level-gentle slope banks may also play a role in buffering adverse effects of flow rises (Moore & Gregory 1988;Grimardias et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Bardonnet et al (1991) found no preference for particular bank profiles. A diel habitat use pattern has been revealed for all fry stages, with a common tendency to colonise at night very shallow, dead zones close to the banks and to rest just above the substrate (Sempeski & Gaudin 1995b).…”
Section: Introductionmentioning
confidence: 99%